Analisis Penggunaan Model Pembelajaran Picture And Picture Pada Mata Pelajaran PKn Di MIN 2 Kota Medan - Annisaa Mawaddah; Sahkholid Nasution; Riris Nurkholidah Rambe (ALFIHRIS : Jurnal Inspirasi Pendidikan, 2023)
The research that has been carried out is entitled "Analysis of the Use of Picture and Picture Learning Models in Civics Subjects at MIN 2 Medan City". Based on the formulation of the problem, this study aims to describe: (1) How is the use of the picture and picture learning model by the teacher in Civics learning in the VA MIN 2 class in Medan City, (2) How active are students in Civics learning using the picture and picture learning model in class VA MIN 2 Medan City. This study uses a qualitative approach. The subjects in this study were VA class homeroom teachers as well as teachers who taught Civics and also VA class students. Data collection techniques in this study used observation, interviews and documentation. Data analysis techniques used in this study are data reduction, data presentation and conclusion. The results of the study revealed that (1) The use of the picture and picture learning model applied by the teacher in Civics learning in the VA MIN 2 class in Medan City was divided into three stages, namely: the opening, core and closing stages. In the core activity, the teacher's stage uses the picture and picture model in a wayintroducing learning material and conveying the learning objectives to be achieved, explaining Civics learning materials, presenting pictures related to learning materials, arranging scrambled pictures, presenting or explaining the reasons for compiling pictures. (2) The activity of students in learning Civics by using the picture and picture learning model in the VA MIN 2 class in Medan City includes: being enthusiastic about participating in learning, listening to and paying attention to teacher explanations, daring to answer questions, daring to present the results of their understanding in front of the class, students participating in doing group discussions, and participate in carrying out learning assignments.